Psychometric properties of the experiences of maternity care scale among Iranian women - Elham Jafari; Mohammad Asghari-Jafarabadi; Mojgan Mirghafourvand; Sakineh Mohammad-Al (BMC, 2024)
Abstract Background Assessing women's perceptions of the care they receive is crucial for evaluating the quality of maternity care. Women's perceptions are influenced by the care received during pregnancy, labour and birth, and the postpartum period, each of which with unique conditions, expectations, and requirements. In England, three Experience of Maternity Care (EMC) scales - Pregnancy, Labour and Birth, and Postnatal - have been developed to assess women's experiences from pregnancy through the postpartum period. This study aimed to validate these scales within the Iranian context. Methods A methodological cross-sectional study was conducted from December 2022 to August 2023 at selected health centers in Tabriz, Iran. A panel of 16 experts assessed the qualitative and quantitative content validity of the scales and 10 women assessed the face validity. A total of 540 eligible women, 1-6 months postpartum, participated in the study, with data from 216 women being used for exploratory factor analysis (EFA) and 324 women for confirmatory factor analysis (CFA) and other analyses. The Childbirth Experience Questionnaire-2 was employed to assess the convergent validity of the Labour and Birth Scale, whereas women's age was used to assess the divergent validity of the scales. Test-retest reliability and internal consistency were also examined. Results All items obtained an impact score above 1.5, with Content Validity Ratio and Content Validity Index exceeding 0.8. EFA demonstrated an excellent fit with the data (all Kaiser-Meyer-Olkin measures > 0.80, and all Bartlett's p < 0.001). The Pregnancy Scale exhibited a five-factor structure, the Labour and Birth Scale a two-factor structure, and the Postnatal Scale a three-factor structure, explaining 66%, 57%, and 62% of the cumulative variance, respectively, for each scale. CFA indicated an acceptable fit with RMSEA ≤ 0.08, CFI ≥ 0.92, and NNFI ≥ 0.90. A significant correlation was observed between the Labour and Birth scale and the Childbirth Experience Questionnaire-2 (r = 0.82, P < 0.001). No significant correlation was found between the scales and women's age. All three scales demonstrated good internal consistency (all Cronbach's alpha values > 0.9) and test-retest reliability (all interclass correlation coefficient values > 0.8). Conclusions The Persian versions of all three EMC scales exhibit robust psychometric properties for evaluating maternity care experiences among urban Iranian women. These scales can be utilized to assess the quality of current care, investigate the impact of different care models in various studies, and contribute to maternal health promotion programs and policies.